In‐vivo hemodynamic imaging of acute prenatal ethanol exposure in fetal brain by photoacoustic tomography. Issue 5 (13th February 2020) - Shan, Tianqi; Zhao, Yuan; Jiang, Shixie; Jiang, Huabei
Abstract: Prenatal ethanol exposure (PEE) can lead to structural and functional abnormalities in fetal brain. Although neural developmental deficits due to PEE have been recognized, the immediate effects of PEE on fetal brain vasculature and hemodynamics remain poorly understood. One of the major obstacles that preclude the rapid advancement of studies on fetal vascular dynamics is the limitation of the imaging techniques. Thus, a technique for noninvasive in‐vivo imaging of fetal vasculature and hemodynamics is desirable. In this study, we explored the dynamic changes of the vessel dimeter, density and oxygen saturation in fetal brain after acute maternal ethanol exposure in the second‐trimester equivalent murine model using a real‐time photoacoustic tomography system we developed for imaging embryo of small animals. The results indicate a significant decrease in fetal brain vessel diameter, perfusion and oxygen saturation. This work demonstrated that PAT can provide high‐resolution noninvasive imaging ability to monitor fetal vascular dynamics. Abstract : We studied the dynamic changes of the vessel diameter, density and oxygen saturation in fetal brain after acute maternal ethanol exposure in the second‐trimester equivalent murine model using a real‐time photoacoustic tomography (PAT) system we developed for imaging embryo of small animals. The results demonstrated the advantages of PAT over other imaging techniques in visualizing fetal vasculature and hemodynamics for studying the pathophysiology of fetal alcohol spectrum disorders.